MICROCIRCULATION AND SARS-COV-2 INFECTION: A FOLLOW UP STUDY. (June 2022) - Malerba, Paolo; Rosei, Claudia Agabiti; Chiarini, Giulia; Nardin, Matteo; Petelca, Alina; Gaggero, Andrea; Lemoli, Matteo; Famà, Francesca; Boari, Gianluca Edoardo; Baresi, Mattia; Bondioli, Nicolò; Porteri, Enzo; et al.
Abstract : Objective: SARS-CoV2 infection can lead to several clinical scenarios, named COVID-19, ranging from mild manifestations to acute respiratory distress syndrome (ARDS), coagulation alterations and endothelial dysfunction. The functional impairment of the microcirculation seems play a key role in the pathophysiology and clinical consequences of COVID-19. However, to date there is no evidence of structural microvascular damage related to COVID-19. Design and method: The aim of this study is to investigate microvascular alterations by adaptive optics and vide-ocapillaroscopy in patients recently admitted for COVID-19 and re-evaluated one year later. Methods: We enrolled 153 patients admitted between February and April 2020 at the Hospital of Montichiari (Brescia) and at the Internal Medicine Department of ASST Spedali Civili - University of Brescia for respiratory failure due to SARS-CoV2-related interstitial pneumonia. Patients were evaluated two months after nalysedsation and after one year. All patients underwent a venous blood sampling for hematochemical tests, evaluation of retinal arteriolar morphology by adaptive optics, assessment of basal and total capillary density (BCD and TCD respectively) at the dorsum of the fourth finger of the non-dominant hand by videocapillaroscopy. Results: Fifty patients with completed follow-up were nalysed. An increase of internal lumen (93.8 ± 13.3 vs. 97.3 ± 14.2 micron, p < 0.001) and a reduction of wall to lumen ratio (WLR 0.30 ± 0.03 vs. 0.27 ± 0.03, p < 0.001) were observed at the follow up visit after one year (Figure). No significant differences were observed in BCD in the dorsum of the finger after one year, whereas a significant reduction in TCD was observed (p < 0.001). Microvascular changes were independent of body mass index and the presence of hypertension or diabetes mellitus. Conclusions: Preliminary data from this study show that patients with SARS-Cov2 infection present an improvement of microvascular structure after one year from the disease, such as a reduction in WLR of retinal arterioles. This suggests that COVID19 might induce structural alterations in the microcirculation which contribute to vascular damage. These changes do not seem to be influenced by the weight, presence of hypertension or diabetes.